TMAO metaorganismal pathway and chronic inflammatory diseases - Zeneng Wang; Shumei Man; Robert Koeth (Exploration of Medicine)
Nutrients containing a trimethylamine (TMA) moiety in their structure can be metabolized by the gut microbiota through enzymatic cleavage of the C-N bond, producing TMA. In the liver, TMA is subsequently oxidized to trimethylamine N-oxide (TMAO) by flavin monooxygenases (FMOs). TMAO exerts pro-atherogenic and pro-inflammatory effects that contribute mechanistically to several chronic inflammatory diseases including cardiovascular disease, chronic kidney disease, obesity, non-alcoholic fatty liver disease, and neurodegenerative diseases. Targeting this metaorganismal pathway may offer substantial health benefits in the prevention and treatment of chronic inflammatory conditions.